Consumer Awareness Towards Rainwater Harvesting System in Selangor, Malaysia - M. Aminuddin, Normadihah; Afgani @ Eusoff, Yendo; Adeena Raslee, Nor; Puad Mat Som, Ahmad (International Journal of Engineering and Technology, 2018)
Reusing water and implementing rainwater-harvesting system are an effective way to reduce the usage of treated water at home. A study on consumerâ€™s awareness towards Rainwater Harvesting System (RWHS) in urban areas of Malaysia is less explored among researchers. This study was to identify the level of consumerâ€™s awareness on RWHS among domestic water users in Gombak District, Selangor. Quantitative approaches were applied through individual distribution of structured questionnaires to 397 domestic water users in the study area from December 2016 to February 2017. The data was analyzed using SPSS version 21. Based on the results of quantitative analysis, four major constructs emerged namely â€˜the advantages of RWHSâ€™, â€˜alternative water sourcesâ€™, â€˜consumersâ€™ concernâ€™ and â€˜consumersâ€™ willingnessâ€™. The total mean scores (total average score) for each construct in ascending order are 3.48 for consumers' readiness, 3.81 for advantages of RWHS, 3.98 for alternative source, and 4.09 for consumers' concern. The findings provide important contribution to water conservation practices in the country as RWHS is considered greener, more efficient, more self-reliant with sound technology.Â Â